(untitled) (Journal of Economic Research & Business Administration, 2020)
The competitiveness of the national economy is one of the most important economic concepts. There are many of its definitions and methods of measurement. Since the country’s competitiveness is formed by a huge number of factors, a literature review was carried out, as a result of which macroeconomic factors affecting the competitiveness of the economy were selected. The purpose of the article is to assess the degree of influence of selected factors on the global competitiveness of countries. For this, panel data of 60 countries for the period from 2006 to 2018 were collected. Based on this data, a regression analysis of panel data with fixed and random effects was carried out, where the dependent variable is the Global Competitiveness Index, and 22 macroeconomic factors act as independent variables. The Hausman test confirmed the preference for using a panel data model with fixed effects over a panel data model with random effects. As a result, 2 models were constructed that showed the degree of influence of the following factors to change the global competitiveness index: gross capital formation, total factor productivity, average labor productivity, pace of inflation rate, share of the current account balance in GDP, share of the employed population in the total population of the country, oil prices, growth rate of oil prices.